Oesophageal perforation: an unusual complication of a hypoglycaemic episode. - Daya, H (1993)
A case of spontaneous oesophageal rupture following vomiting, secondary to a hypoglycaemic episode is reported. The case is of interest in its presentation and physical signs. It reflects the difficulty in diagnosing a condition associated with considerable morbidity and mortality. The importance of recognition of a pattern of symptoms, physical signs and radiographic findings is emphasized.